Improving the Packet Delivery Performance for Concurrent Packet Transmissions in WSNs - Park, Jongjun; Jeong, Jongsoo; Jeong, Hoon; Liang, Chieh-Jan Mike; Ko, JeongGil (IEEE Communications Letters, 2013)
In this letter, we investigate the properties of packet collisions in IEEE 802.15.4-based wireless sensor networks when packets with the same content are transmitted concurrently. While the nature of wireless transmissions allows the reception of a packet when the same packet is transmitted at different radios with (near) perfect time synchronization, we find that in practical systems, platform specific characteristics, such as the independence and error of the crystal oscillators, cause packets to collide disruptively when the two signals have similar transmission powers (i.e., differences of <2 dBm). In such scenarios, the packet reception ratio (PRR) of concurrently transmitted packets falls below 10%. Nevertheless, we empirically show that the packet corruption patterns are easily recoverable using forward error correction schemes and validate this using implementations of RS and convolutional codes. Overall, our results show that using such error correction schemes can increase the PRR by more than four-fold.